Event-related potentials in insomnia reflect altered perception of sleep. Issue 10 (1st June 2021) - Feige, Bernd; Baglioni, Chiara; Boehm, Philipp; Heinrich, Anna; Trumm, Samuel; Benz, Fee; Nissen, Christoph; Domschke, Katharina; Frase, Lukas; Riemann, Dieter
Abstract: Study Objectives: Insomnia is defined by the subjective complaint of poor sleep as well as daytime impairments. Since polysomnography (PSG) typically shows only modest sleep impairment, some still unidentified property of sleep, not mirrored in PSG, may be modified in insomnia. One possible mechanistic hypothesis is that insomnia patients may be more sensitive to inevitably occurring internal or external stimuli during the night, causing brief sleep disruptions then perceived as wake time. Methods: Auditory event-related potentials (ERP) to low intensity (50 dB SPL) synthesized guitar tones played continuously throughout two nights of polysomnographically registered sleep were obtained in fifty patients with insomnia disorder (ID, without comorbidities) and 50 age- and sex-matched good sleeper controls (GSC) for each sleep stage and NREM/REM cycle. Phasic and tonic REM were treated as separate stages. Latencies and amplitudes of components P1, N1 and P2 were measured and analyzed by multivariate repeated-measures ANCOVA including effects of group, night, cycle, and age. Results: ID showed reduced P2 amplitudes relative to GSC specifically in phasic REM sleep. The same reduction also correlated with the amount of sleep misperception across groups. Independent component analysis showed a frontal negativity to contribute most to this group difference. Conclusions: The present finding can be interpreted as increased mismatch negativity (MMN) in ID, reflecting automated detection of change in the auditory system and a concomitant orienting response. Specifically phasic REM sleep appears to be vulnerable to sensory afferences in ID patients, possibly contributing to the perception of being awake. Clinical Trial Information: Short name "PERSLEEP 2, " URL https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00008965, Registration DRKS00008965.